By Bits and Pieces: The Contributions of Zoos and Aquariums to Science and Society via Biomaterials - David M. Powell; Theodore G. Meyer; Mary Duncan (Journal of Zoological and Botanical Gardens, 2023)
Scientific research has long been recognized as one of the four pillars of the zoo or aquarium mission, alongside recreation, conservation, and education. This study sought to quantify a sample of zoos’ participation in scientific research via the provision of biomaterials from animals to outside scientists and the associated training of undergraduate and graduate students that resulted from these projects. A convenience sample of zoos provided data on their participation in biomaterials-related projects and a focused analysis of biomaterials-related research facilitated by the Saint Louis Zoo was conducted. In addition, the Association of Zoos & Aquariums’ conservation & science database was queried to uncover what research projects AZA members engaged in over the last five years that likely involved biomaterials research and training of students. Results demonstrate that zoos are making significant contributions to science by agreeing to participate in large numbers of biomaterials-related projects across different areas of focus involving a variety of animal species annually, with results applicable to human and non-human animals. Support of such research often involves student thesis projects, thus contributing to the education of future scientists.